Elaboração de novo produto gelificado à base de extrato hidrossolúvel da amêndoa da castanha de caju: estudo dos parâmetros sensoriais - Costa, Vanderson da Silva (2013)
Considering the economic importance of cashews nuts for the state of Ceará, Brazil's main exporter of this product and the high percentage of broken kernels during processing Chestnut considerably decreases the profit-making in this sector, it is necessary to search for new alternatives for utilization of this raw material as a way of adding value to it. Thus , this research aimed to develop a product based on watersoluble extract of almond cashew (EHACC) and blend of guar gum/carrageenan (CG) using the orthogonal factorial design 2² with three central points and the technique of response surface for optimization of sensory characteristics. By applying affective sensory testing scale relative to the ideal and structured hedonic scale of nine points , the center point of the formulations with different percentages of sucrose were evaluated for selecting the optimal sucrose concentration by linear regression analysis , analysis of the ideality firmness and acceptance of attributes color, aroma, texture, flavor and overall impression . The formulations of the experimental design with the addition of the ideal percentage of sucrose were analyzed in relation to global hedonic acceptance and ideality of visual texture, manual and oral texture texture. The optimal concentration was 22 % sweetness of sucrose. There was a trend of increasing acceptance at the midpoint of a 0,3g/100mL guar/carrageenan in 50:50 experimental design. The visual texture evaluation showed that the higher the concentration of hydrocolloids, most ideality. In the evaluation of manual and oral texture none of the samples reached 70 % of ideality. Thus, the combination of quantity and proportion of the blend midpoint contributed to greater acceptance of gelled product features and good acceptance tested showed a potential for commercial success for future marketing of the product.